Assessing the Longitudinal outcomes of Piperacillin/tazobactam versus ceftriAxone and metronidazole for Children with perforated Appendicitis (ALPACA): A protocol for a pilot randomized controlled trial - Daniel Briatico; Nadia Safa; Helene Flageole; Sarah Khan; Jeffrey Pernica; Mohamed Eltorki; Eyal Cohen; Michael H. Livingston (PLoS ONE, 2025)
Background Acute appendicitis is the most common indication for emergency surgery in children. In cases of perforation, patients require post-operative intravenous antibiotics in hospital. However, some children fail to respond adequately, resulting in prolonged hospitalization. The optimal antibiotic regimen for perforated appendicitis remains uncertain. Methods We propose a double-blind, randomized controlled pilot trial comparing two commonly used antibiotic strategies. Eligible participants include children <18 years undergoing laparoscopic appendectomy for perforated appendicitis. Following surgery, participants will be randomized to receive either: (1) piperacillin/tazobactam; or (2) ceftriaxone and metronidazole. The sample size for the pilot study is 16 participants (i.e., 8 per group). Feasibility outcomes include recruitment rate, protocol adherence, loss to follow-up, and cost per participant. Discussion This pilot study will assess the feasibility of conducting a blinded randomized controlled trial of postoperative antibiotic therapy in children with perforated appendicitis. To date, only one randomized trial has addressed this question, but it was limited by its single-center design, lack of blinding, and susceptibility to ascertainment bias and other methodological concerns. Findings from this pilot will inform the design of a larger, multicenter study with rigorous blinding and standardized outcome assessment to determine whether piperacillin-tazobactam or ceftriaxone and metronidazole provides superior outcomes. Trial Registration ClinicalTrials.gov: NCT05943223